Formulating the Novelty of Communication Research in Post-Covid-19 Era - Agustina Multi Purnomo (Faculty of Social Sciences and Humanities Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2025)
This study aimed to uncover innovative research topics about communication in the post-Covid-19 pandemic. Bibliometric analysis depicted research topic trends within a certain period from big data and online publications on specific sites to find research novelties. Data analysis used VosViewer. Several 1000 of the most relevant 5562 articles were analyzed using network, overlay, and density visualization. Network visualization analysis found 12 clusters with 13 communication topics. Further analysis indicated that three communication topics emerged as central themes. Novelty research was possible on other issues such as public relations, internal communication, communication theory, science communication, misinformation, and public opinion. An overlay visualization analysis revealed eight topics that lacked communication themes in recent COVID-19 research. However, opportunities for novel research were found in issues like information and communication technologies, crisis communication, public relations, internal communication, communication theory, science communication, and public opinion. The density visualization analysis revealed that previous studies focused on communication, risk communication, and social media. Therefore, this study suggests that future communication research during the post-COVID-19 recovery period should explore information and communication technologies, crisis communication, public relations, internal communication, communication theory, science communication, and public opinion.